(untitled) (Advances in Civil and Architectural Engineering, 2024)
Sustainability encompasses environmental, economic, and social dimensions, with safety standing as a crucial facet within the construction industry’s social sustainability framework. This study addresses this vital concern by comprehensively analyzing published research on prominent safety risk factors and effective mitigation measures in construction projects, considering their influence on the industry’s sustainability. A systematic literature review spanning 2008 to 2023 examined 32 pertinent articles from reputable journals. The review revealed 25 identified safety risk factors and 20 corresponding effective measures. These were categorised into labour, environmental, technical, and financial risks, forming the basis for a network diagram illustrating their interrelationships and associated mitigation strategies. Moreover, the study introduced a sustainability criterion, evaluating the various safety risk factor categories, and highlighting labour and environmental risks as the most significant concerns among the factors assessed. Finally, the research proposes future research directions aimed at elevating safety and sustainability within construction projects.